Study on the performance and control of a piezo-actuated nozzle-flapper valve with an isothermal chamber - Kamali, Mohammadreza (Strojniški vestnik, 2016)
A new integrated nozzle-flapper valve equipped with a piezoelectric actuator and an isothermal chamber has been developed and studied in detail. The designed single stage valve controls the pressure and flow rate simply, effectively, and separately. This idea can easily be used in the pilot stage of a two-stage valve as well. Application of isothermal condition in the valve load chamber eliminates the dynamic malfunction that may persist from temperature variation within the valve load chamber; consequently, the governing equations for the prediction of pressure dynamics in the chamber are much more accurate and simpler. The valve has been equipped with a stacked type piezoelectric actuator which has a unique behaviour. Furthermore, stiffness, in the selected actuator, is enhanced against the thrust of the discharging flow from the nozzle, thus decreasing the complexity of dynamic equations of the valve. A detail mathematical model and simulation was developed to study the dynamic performance analysis of the proposed valve. An experimental test rig was built to validate the results of simulations. The unique features and performance of the proposed valve were studied thoroughly. The valve's governing equations are nonlinear in nature, and some variables of the equations are a source of some uncertainties; sliding mode approach was used to control the steady and unsteady pressure and output flow rate of the valve.
Keywords: drseči pristop; generatorji pretoka; izotermne komore; piezoelektrični aktuatorji; ventili s šobo in odbojno ploščico; ventili za regulacijo tlaka